Lectotypification of Lagerstroemia tomentosa (Lythraceae) and a note on its distribution in India - Sivadas, Deepu; Geethakumary, M.p.; Pandurangan, A.g. (Phytotaxa, 2016)
During a study of distribution of Lagerstroemia Linnaeus (1759: 1068) in South India, we encountered a material from Neriyamangalam, Ernakulam District, Kerala, which was identified as Lagerstroemia tomentosa C. Presl. (1844: 142), a species not known to occur in the Western Ghats. On examining the protologue of the species and a later revision of the genus by Furtado and Srisuko (1969), along with specimens housed at various herbaria, we identified the need for lectotypification of the species.